Covering All the Bases: Complementary MR1 Antigen Presentation Pathways Sample Diverse Antigens and Intracellular Compartments - Kulicke, Corinna; Karamooz, Elham; Lewinsohn, David; Harriff, Melanie (Frontiers in Immunology, 2020)
The ubiquitously expressed, monomorphic MHC class Ib molecule MHC class I-related protein 1 (MR1) presents microbial metabolites to mucosal-associated invariant T (MAIT) cells. However, recent work demonstrates that both the ligands bound by MR1 and the T cells restricted by it are more diverse than originally thought. It is becoming increasingly clear that MR1 is capable of presenting a remarkable variety of both microbial and non-microbial small molecule antigens to a diverse group of MR1-restricted T cells (MR1Ts) and that the antigen presentation pathway differs between exogenously delivered antigen and intracellular microbial infection. These distinct antigen presentation pathways suggest that MR1 shares features of both MHC class I and MHC class II antigen presentation, enabling it to sample diverse intracellular compartments and capture antigen of both intracellular and extracellular origin. Here, we review recent developments and new insights into the cellular mechanisms of MR1-dependent antigen presentation with a focus on microbial MR1T cell antigens.